Temporal dynamics of cortical activity and postural control in response to the first levodopa dose of the day in people with Parkinson's disease - Araújo-Silva, Fabiana [UNESP]; Santinelli, Felipe B. [UNESP]; Felipe I. Imaizumi, Luis [UNESP]; Silveira, Aline P.B. [UNESP]; Vieira, Luiz H.P. [UNESP]; Alcock, Lisa; Barbieri, Fabio A. [UNESP] (Elsevier, 2022)
Background: Our understanding of how balance control responds to levodopa over the course of a single day in people with Parkinson's disease (PD) is limited with the majority of studies focused on isolated comparisons of ON vs. OFF levodopa medication. Objective: To evaluate the temporal dynamics of postural control following the first levodopa dose of the day during a challenging standing task in a group of people with PD. Methods: Changes in postural control were evaluated by monitoring cortical activity (covering frontal, motor, parietal and occipital areas), body sway parameters (force platform), and lower limb muscle activity (tibialis anterior and gastrocnemius medialis) in 15 individuals with PD during a semi-tandem standing task. Participants were assessed during two 60 second trials every 30 minutes (ON-30 ON-60 etc.) for 3 hours after the first matinal dose (ON-180). Results: Compared to when tested OFF-medication, cortical activity was increased across all four regions from ON-60 to ON-120 with early increases in alpha and beta band activity observed at ON-30. Levodopa was associated with increased gastrocnemius medialis activity (ON-30 to ON-120) and ankle co-contraction (ON-60 to ON-120). Changes in body sway outcomes (particularly in the anterior-posterior direction) were evident from ON-60 to ON-120. Conclusions: Our results reveal a 60-minute window within which postural control outcomes may be obtained that are different compared to OFF-state and remain stable (from 60-minutes to 120-minutes after levodopa intake). Identifying a window of opportunity for measurement when individuals are optimally medicated is important for observations in a clinical and research setting.
Keywords: Brain activity; Electroencephalography; Medication; Muscle activity; Parkinson's disease; Posture